The Mapping of Plumeria Eco Park Potencies as a New Tourism Destination in Muara Enim, South Sumatera (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
In today's digitalized world, written information is essential because eco-parks offer a variety of tourist attractions in one convenient location. Established in the regency, Plumeria Eco Park is a large eco-park located in Muara Enim. Its sustainability can be attained by collaborations by determining the potencies through a community service initiative. The purpose of this project was to map Plumeria Eco Park's potential as a new tourist attraction in Muara Enim to produce English-language content for its upcoming website eventually. Descriptive qualitative analysis through observation and interviewing was the methodology employed. For the potency mapping, every area within the eco-park was observed. Interviews were conducted with the owner and staff to get potency-related information. The mapping approach focused on five aspects of tourist destination potential: attraction, activities, amenities, accessibility, and accommodation. After the procedure, the results showed that Plumeria Eco Park could become the new tourism destination in Muara Enim since it fits the five criteria. This community service project is expected to help grow Plumeria Eco Park shortly as the first stage of a content-writing website.